Out of the deep - Skurzynski, Gloria; Ferguson, Alane (Washington, D.C. : National Geographic Society, 2002)
Jack, Ashley, and their unreliable new foster sister set out to solve the mystery of why whales are beaching themselves at Acadia National Park.
740
Keywords: Whales -- Fiction; Foster home care -- Fiction; National parks and reserves -- Fiction; Mystery and detective stories; Acadia National Park (Me.) -- Fiction